2019
DOI: 10.1007/s41745-019-00137-5
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Pair Motion Due to Double Hydrogen Bonding: The Formic Acid Dimer Case

Abstract: | Formic acid dimer as the prototypical doubly hydrogenbonded gas-phase species is discussed from the perspective of the three translational and the three rotational degrees of freedom which are lost when two formic acid molecules form a stable complex. The experimental characterisation of these strongly hindered translations and rotations is reviewed, as are attempts to describe the associated fundamental vibrations, their combinations, and their thermal shifts by different electronic structure calculations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 110 publications
1
48
0
Order By: Relevance
“…Contrary to that, a 24-mode VSCF/VCI calculation on a PES calculated at the CCSD(T)-F12a/haTZ level of theory and fit to permutationally invariant polynomials 40 correctly describes the spectroscopy and increased width of the OH-stretch band. 43 The present work also allows to make contact with a recent assessment 35 of various sources of errors in the spectroscopy and thermodynamics of FAD which reported that ''More often than not, the overestimation of harmonic downshifts in DFT is qualitatively compensated by the inability of classical dynamics to sample the anharmonic region probed by the quantum nature of the hydrogen atom. This frequently provides right answers for the wrong reasons whenever high-frequency XH stretching spectra are simulated, because in this case, temperatures of several 1000 K would be needed to sample the relevant fundamental vibrational displacements.''…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Contrary to that, a 24-mode VSCF/VCI calculation on a PES calculated at the CCSD(T)-F12a/haTZ level of theory and fit to permutationally invariant polynomials 40 correctly describes the spectroscopy and increased width of the OH-stretch band. 43 The present work also allows to make contact with a recent assessment 35 of various sources of errors in the spectroscopy and thermodynamics of FAD which reported that ''More often than not, the overestimation of harmonic downshifts in DFT is qualitatively compensated by the inability of classical dynamics to sample the anharmonic region probed by the quantum nature of the hydrogen atom. This frequently provides right answers for the wrong reasons whenever high-frequency XH stretching spectra are simulated, because in this case, temperatures of several 1000 K would be needed to sample the relevant fundamental vibrational displacements.''…”
Section: Discussionmentioning
confidence: 77%
“…This confirms earlier findings and is related to the fact that MD simulations at 300 K do not sample the mechanical anharmonicity of XH stretch or any other strongly anharmonic modes sufficiently to give reliable frequencies from such an approach. Contrary to that, a 24-mode VSCF/VCI calculation on a PES calculated at the CCSD(T)-F12a/haTZ level of theory and fit to permutationally invariant polynomials 40 correctly describes the spectroscopy and increased width of the OH-stretch band.present work also allows to make contact with a recent assessment35 of various sources of errors in the spectroscopy and thermodynamics of FAD which reported that "More often than not, the overestimation of harmonic downshifts in DFT is qualitatively compensated by24 Page 24 of 42 Physical Chemistry Chemical Physics Physical Chemistry Chemical Physics Accepted Manuscript Open Access Article. Published on 26 October 2021.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…However, the interpretation of the IR spectra, especially in the O-H stretching region has been difficult due to vibrational coupling, tunneling-splitting, and anharmonicity. [4][5][6][7][8][9][10][11] One of the interesting models to interpret the IR spectra in the O-H stretching region of carboxylic acid dimers is monomers in the dimer model. 12 However, the role of hydrogen bonding in the interpretation of these spectra has been reduced to tuning the OH stretching vibration in and out of resonance with combinations of the remaining vibrational modes of the COOH functional group.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interpretation of the IR spectra, especially in the O-H stretching region, has been difficult due to vibrational coupling, tunneling-splitting, and anharmonicity. [4][5][6][7][8][9][10][11] One of the interesting models to interpret the IR spectra in the O-H stretching region of carboxylic acid dimers is monomers in the dimer model. 12 However, the role of hydrogen bonding in the interpretation of these spectra has been reduced to tuning the OH stretching vibration in and out of resonance with combinations of the remaining vibrational modes of the COOH functional group.…”
Section: Introductionmentioning
confidence: 99%